Occupational Stress and Job Performance among academics in Indonesia - Nur Prayogi, Gios; Hakiki, Rizky; Zulhazmi Abdul Rashid, Aimi (International Journal of Psychosocial Rehabilitation, 2020)
Cambridge dictionary explains that occupational stress is caused by work or activity. Stress can also be described as a great worry, which is a difficult situation or something which causes this condition. In this research, researchers want to explore the effect of relationship, environment, and workload to stress which is to see the weather it gives an impact on the job performance among academic staff university or not significant. Besides that, other researchers define that stress related to work is a response which people receive when presented with the work pressure and demands which are not matched to their abilities and knowledge and which challenges their ability to cope. The factors evaluated are relationship, environment, workload is one of factors are contribute to occupational stress and these factors may have an impact on job performance.